2009
DOI: 10.1111/j.1600-079x.2009.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of matrix metalloproteinase‐9 and ‐3 in nonsteroidal anti‐inflammatory drug‐induced acute gastric ulcers in mice: regulation by melatonin

Abstract: The pathogenesis of gastric ulcer is associated with remodeling of extracellular matrix (ECM) by various matrix metalloproteinases (MMPs). However, how MMPs are regulated during nonsteroidal anti-inflammatory drug (NSAID)-induced acute gastric ulceration is not well studied. In this study, different NSAIDs (80 mg/kg b.w.) were applied to generate acute gastric ulcer in the BALB/c mouse and the regulation of MMPs were investigated. NSAIDs caused dose-dependent induction in MMP-9 and -3 activities and expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 48 publications
3
36
0
Order By: Relevance
“…Melatonin (Mel) is an endogenous antioxidant, and its metabolites are potent free radical scavengers, indirect antioxidants [35, 36], and an anti-inflammatory agent [37, 38]. Recently, Melatonin showed protection against exogenous β -amyloid deposition induced mitochondrial dysfunction and other neurodegenerative disease models [3941].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (Mel) is an endogenous antioxidant, and its metabolites are potent free radical scavengers, indirect antioxidants [35, 36], and an anti-inflammatory agent [37, 38]. Recently, Melatonin showed protection against exogenous β -amyloid deposition induced mitochondrial dysfunction and other neurodegenerative disease models [3941].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic actions of melatonin were further expanded when it was shown that melatonin also ameliorates inflammation by blocking transcriptional factors and inhibiting the transcriptional activation of proinflammatory cytokines including tumor necrosis factor (TNF)-α, interleukin (IL)-1 Sasaki et al, 2002) and inflammatory enzymes such as COX-2, iNOS (Deng et al, 2006;Dong, 2003) and matrix metalloproteinases (MMPs) (Esposito et al, 2008a;Ganguly and Swarnakar, 2009;Swarnakar et al, 2011) by blocking NF-κB binding to DNA (Chuang et al, 1996;Natarajan et al, 1995). Several reports have addressed the mechanisms that are involved in genomic actions of melatonin.…”
Section: Gene Regulation By Melatonin Under Nitrooxidative Stress Conmentioning
confidence: 96%
“…In terms of its action on the immune system, melatonin modulates key biological factors, which include inflammatory cytokines [36]. Furthermore, it has been shown that melatonin inhibited in vivo the expression of iNOS in liver and lung of LPS‐treated rats [37], and in carrageenan‐treated rats [38], and downregulated matrix metalloproteinase‐9 and ‐3 in nonsteroidal anti‐inflammatory drug‐induced acute gastric ulcers in mice [39]. In addition, melatonin inhibited LPS‐induced increase of COX‐2 protein expression in RAW 264.7 macrophages [40].…”
Section: Introductionmentioning
confidence: 99%